Validity of Waist-to-Height Ratio for Hypertension Screening among Pre-Elderly Men and Women in Indonesia - Rusydiana, Hamidah Aula; Nurwati, Yuni (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
The research was conducted to validate the Waist-to-Height Ratio (WHtR) as a predictor of hypertension among pre-elderly individuals in Indonesia. The study utilized a cross-sectional analysis based on secondary data from the 2023 Indonesian Longitudinal Aging Survey (ILAS). A total of 2,170 pre-elderly adults aged 45–59 years (993 men and 1,177 women), were included, with 46.4% classified as hypertensive. Predictive performance of WHtR was assessed using Receiver Operating Characteristic (ROC) analysis. Optimal cutoff points were then determined using Youden index and accuracy. Diagnostic performance was evaluated based on sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Values (NPV). The Area Under the Curve (AUC) of WHtR for the predicting hypertension was 0.648 (95% CI: 0.614–0.683, p<0.001) in men and 0.633 (95% CI: 0.601–0.664, p<0.001) in women. The selected cutoff for WHtR was 0.513 in men (sensitivity: 67.6%, specificity: 55.5%), and 0.597 in women (sensitivity: 56.3%, specificity: 65.3%), with an overall accuracy of 61.0%. These results support that WHtR may serve as a practical screening tool for hypertension in pre-elderly individuals in Indonesia, with sex-specific cutoff values that could support early identification and prevention strategies.